EFEKTIVITAS PERAN UNDANG-UNDANG CIPTA KERJA DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP PEKERJA - Syukron Kadir (Universitas Karya Husada Semarang, 2023)
The Job Creation Law which uses the Omnibus Law method has the aim of increasing investment and making industrialization in Indonesia more advanced. The efforts that are being made include cutting the bureaucratization route and making it difficult to permit new activities. As a source of law, of course the Job Creation Law must be able to answer and resolve problems that occur related to employment. So that the Job Creation Law will have an impact on workers, so the issue raised is What are the Implications of the Job Creation Law on legal protection for workers. Through a normative juridical approach using primary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Later it will be elaborated on every statutory regulation related to legal theory as an object of research. Based on the analysis carried out, the content of the material in the Job Creation Law (omnibus law) actually has implications in the form of a decline in the protection and fulfillment of the right to work and a decent living. There are indications that the Job Creation Law has gone backwards compared to (existing) sectoral regulations because it is influenced by the availability factor, this is because it does not provide broad job opportunities for the community, instead it opens the tap for workers from various countries. Apart from that, it is also felt that the Job Creation Law has decreased efforts to protect the right to work and decent wages starting with forcing outsourcing of workers under the pretext of expanding job opportunities and accelerating national strategic projects. The implications of opening jobs that are outsourced are not only related to sustainability and certainty of the right to work, but also have another impact, namely the potential for a decrease in the quality of the working relationship between employers and workers.